Sinalização visual e biologia reprodutiva de Dendropsophus werneri (Anura: Hylidae) em área de Mata Atlântica no estado do Paraná, Brasil - Miranda, Daniele Bazzo; Garey, Michel Varajão [UNESP]; Monteiro-Filho, Emygdio L. A.; Hartmann, Marília Teresinha (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2008)
We studied the reproductive biology and visual signaling of Dendropsophus werneri, whose distribution is limited to the Atlantic Rain Forest. The fieldwork was carried out in the Estação 2 do IAPAR, municipality of Morretes, state of Paraná, Brazil, from August 2006 to March 2007. Additional information on reproduction was gathered in the Reserva Natural Salto Morato, municipality of Guaraqueçaba, state of Paraná, Brazil, from September 2006 to March 2007. Males were smaller than females. Males called throughout all the study period in Morretes, but were active only during three months in Guaraqueçaba; males called from low vegetation along the edge of temporary ponds in open areas. The visual signaling was observed in two contexts: (1) aggressive behaviors between two males and (2) during the reproduction, by amplectant males. In the territorial behavior, males exhibited both aggressive and mixed calls, visual signaling as well as physical combats. We also recorded satellite behavior in four males. The mean egg number per clutch was 244 ± 32 eggs, varying between 188 and 310 eggs. We observed two reproductive modes: Mode 1 and Mode 24. In the present study, Dendropsophus werneri showed elaborated social interactions involving visual signaling, territorial behavior, mating bahavior with tactile stimuli, and two different reproductive modes, demonstrating its complex reproductive biology.
Visual signaling and reproductive biology of Dendropsophus werneri (Anura: Hylidae) in the Atlantic Forest, state of Paraná, Brazil
Keywords: Atlantic Forest; Dendropsophus werneri; Reproduction; Visual signals; Anura; Hylidae